Using RCA and the Balanced Scorecard to Assess the firm Performance - Kadhim, Hatem Karim; Abdulzahra, Ali Noori (Akkad Journal of Contemporary Management Studies, 2021)
For the objectives of this article, we wish to underline the significance of resource consumption accounting and the balanced scorecard in today's accounting processes and how they assist an economic unit to work better. Consequently, it indicates that the Balanced Scorecard method may be upgraded by accounting for resource consumption and explains how this enhances performance management efficiency and answers difficulties concerning complementing views. Researchers analyzed data from the Najaf men's clothing factory from 2018 and conducted in-depth interviews with department leaders and employees to investigate the economic unit's efficiency. The data was acquired through site visits and personal interviews. As a result, an increase in financial and non-financial indicators' efficiency may be accomplished by combining resource consumption accounting (RCA) with a balanced scorecard (BSC), according to the results (financial, customer, internal operations, and learning and growth perspectives) (financial, customer, internal processes, and learning and growth perspectives) (financial, customer, internal processes, and learning and growth perspectives). Thus, the economic unit of the sample will be granted a superior performance efficiency rating.